(untitled) (Revista de Investigaciones Universidad del Quindío, 2011)
Biofuels, like ethanol, have now become an alternative for power generation more environmentally friendly, but his production has shown a number of shortcomings within which are the use of raw materials and food corn and sugarcane, it is therefore necessary to seek alternatives for its production Chayote (citron) is a fruit that has good content of sugar, starch and cellulose, is found in the coffee region and is not considered a staple. For the above in this paper was intended to generate bioethanol based on soluble solids, using Saccharomyces cerevisiae as a leavening agent. The ethanol yield obtained was 52.18 ml/100g of ss and was determined by infrareds pectroscopy.